How does Institutional Setting Affect the Impact of EU Structural Funds on Economic Cohesion? New Evidence from Central and Eastern Europe - Marina Gruševaja; Toralf Pusch (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2011)
Structural Funds are the main instrument of the EU cohesion policy. Their effective use is subject to an ongoing debate in political and scientific circles. European fiscal assistance under this heading should promote economic and social cohesion in the member states of the European Union. Recently, the domestic institutional capacity to absorb, to distribute and to invest Structural Funds effectively has become a crucial determinant of the cohesion process and has attracted attention of the scientific community. The aim of this study is to shed light on the effectiveness of Structural Funds in the countries of the first Central and Eastern European enlargement round in 2004. Using regional data for these countries, we have a look on the impact of several institutional governance variables on the effectiveness of Structural Funds. In the interpretation of results, reference is made to regional economics. Results of the empirical analysis indicate an influence of certain institutional variables on the effectiveness of Structural Funds in the new member states. – – Europäische Strukturfonds sind das wichtigste Instrument der EU-Kohäsionspolitik. Ihre effektive Nutzung wird seit längerem in den politischen und wissenschaftlichen Kreisen diskutiert. Die europäischen Strukturfonds sind auf die wirtschaftliche und soziale Kohäsion ausgerichtet. Sie sollen dazu beitragen, wirtschaftliche und soziale Probleme zu lösen und die wirtschaftliche Entwicklung in den Mitgliedstaaten der Europäischen Union (EU) zu fördern. Insbesondere die inländischen institutionellen Kapazitäten, die europäischen Finanztransfers zu absorbieren, zu verbreiten und effektiv zu investieren, werden zunehmend zu einem entscheidenden Faktor für effektive Kohäsionsprozesse, was wir in unserem Beitrag auf den Prüfstand stellen. Ziel ist dabei, die Effektivität der Strukturfonds in den Ländern der ersten EU-Erweiterung um mittel- und osteuropäische Länder im Jahr 2004 zu analysieren. Anhand dieser Länder werden die Effekte verschiedener institutioneller Variablen auf die Wirksamkeit der Strukturfonds auf regionaler Ebene untersucht. In der Interpretation unserer Ergebnisse beziehen wir uns zusätzlich auf die Regionalökonomie. Das Ergebnis der empirischen Analyse zeigt den Einfluss bestimmter institutioneller Variablen auf die Effektivität der Strukturfonds in den neuen Mitgliedstaaten der EU.
urn:nbn:de:101:1-201112215420
Keywords: R11; P2; O38; 330; EU cohesion policy; Structural Funds; institutional setting; EU new member states; EU-Kohäsionspolitik; Strukturfonds; Institutionen; Neue EU-Mitgliedsländer; EU-Strukturfonds; Entwicklungskonvergenz; Institutionalismus; Wirkungsanalyse; EU-Staaten (Osteuropa)